2005
DOI: 10.1002/pros.20385
|View full text |Cite
|
Sign up to set email alerts
|

Expression of prothymosin alpha is correlated with development and progression in human prostate cancers

Abstract: The present study clearly demonstrated that PTMA expression is intimately involved in the differentiation and progression of human prostate cancers, and could be a target for therapy and diagnostic purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 21 publications
2
34
0
4
Order By: Relevance
“…Cheung's group has shown that expression of a considerable number of genes is directly controlled by cis-or trans-acting elements of the genotype (8-10). Many studies have also demonstrated the correlation between gene expression and treatment effect (11)(12)(13)(14)(15)(16)(17)(18)(19). The present study links genotype to gene expression to cell line treatment response and ultimately identified genetic variants that influence drug-induced cytotoxicity.…”
Section: Discussionmentioning
confidence: 92%
“…Cheung's group has shown that expression of a considerable number of genes is directly controlled by cis-or trans-acting elements of the genotype (8-10). Many studies have also demonstrated the correlation between gene expression and treatment effect (11)(12)(13)(14)(15)(16)(17)(18)(19). The present study links genotype to gene expression to cell line treatment response and ultimately identified genetic variants that influence drug-induced cytotoxicity.…”
Section: Discussionmentioning
confidence: 92%
“…In the only article-to our knowledge-reporting on the immunochemical localization of ProTa in prostatic tissue samples, Suzuki et al (2006) studied a large number of normal prostate, benign prostatic hyperplasia, and prostate cancer samples. According to the results of that study, ProTa-like immunoreactivity was observed mainly in the cell nucleus, whereas a weak cytoplasmic staining was also observed; this may be attributed to the antibody the authors used (commercially available monoclonal antibody to ProTa, clone 2F11), which, if identical to the one first described by Sukhacheva et al (2002), recognizes an epitope on the N terminus of the ProTa molecule (aa 1-31) and might, therefore, bind to cytoplasmic Ta1 as well.…”
Section: Discussionmentioning
confidence: 99%
“…Its presence in the nuclear compartment, also supported by the putative bipartite NLS, is well reported in literature and is associated with several functions (Martini and Katzenellenbogen, 2003;Karapetian et al, 2005;Mosoian et al, 2006), including its correlation with development and progression of prostate cancer (Suzuki et al, 2006). In addition, its involvement in chromatin remodeling, owing to the acidic residues clustered in the central part of the molecule, is also described.…”
Section: Prothymosin a Expression In The Frog Testismentioning
confidence: 91%